Assessing feasibility of targeted primary care referrals for patients with clinical suspicion of interstitial lung disease using lung ultrasound: a prospective case finding study. The potential benefits of LUS utilization - Symvoulakis, Emmanouil; Vasarmidi, Eirini; Linardakis, Manolis; Tsiavos, Alexandros; Mantadaki, Aikaterini; Pitsidianakis, Georgios; Karelis, Andreas; Petraki, Chrysi; Nioti, Kadiani; Mastronikolis, Stelios; Tzanakis, Nikolaos; Eraclion Crete, Antoniou K (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: In Primary Health Care (PHC) many interstitial lung disease (ILD) cases may remain at diagnostic delay, due to their challenging presentation and the limited experience of general practitioners (GPs) in recognizing their early symptoms. Objective: We have designed a feasibility study to investigate early ILD case-finding competency between PHC and tertiary care. Methods: A cross-sectional prospective case-finding study was launched at two private health care centers of Heraklion, Crete, Greece, during nine months (2021-2022). After clinical assessment by GP, PHC attenders, who agreed to participate in the study, were referred to the Respiratory Medicine Department, University Hospital of Heraklion, Crete, underwent Lung Ultrasound (LUS) and those with an overall suspicion for ILDs underwent high resolution computed tomography (HRCT) scan. Descriptive statistics and chi-square tests were used. Multiple Poisson regression analysis was performed to explain positive LUS and HRCT decision with selected variables. Results: One hundred and nine patients out of 183 were finally included (54.1% females; mean age 61, SD: 8.3 years). Thirty-five (32.1%) were current smokers. Overall, two out of ten cases were assessed to need HRCT due to a moderate or high suspicion (19.3%; 95%CI 12.7, 27.4). However, in those who had dyspnea in relation to counterparts, a significantly higher percentage of patients with LUS findings (57.9% vs. 34.0%, p=0.013) was found, as in those who had crackles (100.0% vs. 44.2%, p= 0.005). Detected possible ILD provisional labelling cases were 6, and most importantly, 5 of those cases were considered highly suspicious for further evaluation based on LUS findings. Conclusions: This is a feasibility study exploring potentials by combining data of medical history, basic auscultation skills, as crackles detection, and inexpensive and radiation-free imaging technique, such as LUS. Cases of ILD labeling may be hidden within PHC, sometimes, much before any clinical manifestation.